FOLK PEDAGOGY IS A SET OF EDUCATIONAL EXPERIENCES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This article talks about the role and importance of folk pedagogy in the education and upbringing of children, as well as pedagogical factors preserved in folklore, fairy tales, proverbs, children’s games and toys, etc.